2012
DOI: 10.1186/1756-0500-5-37
|View full text |Cite
|
Sign up to set email alerts
|

Understanding unintentional childhood home injuries: pilot surveillance data from Karachi, Pakistan

Abstract: BackgroundChildhood injuries, an important public health issue, globally affects more than 95% of children living in low-and middle-income countries. The objective of this study is to describe the epidemiology of childhood unintentional injuries in Karachi, Pakistan with a specific focus on those occurring within the home environment.MethodsThis was a secondary analysis of a childhood unintentional injury surveillance database setup in the emergency department of the Aga Khan Hospital, Karachi, Pakistan for 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 16 publications
3
24
1
1
Order By: Relevance
“…This proportion is less than one in five reported elsewhere but our sample included only the ED-reported injuries which itself is a significant outcome. This is consistent with another hospital-based study from Pakistan which showed that school injuries contribute towards 5% of unintentional injuries among children less than 11 years of age [20]. The National annual incident rate for school injuries in Pakistan is 1.6 per 1 000 per year [15].…”
Section: Discussionsupporting
confidence: 87%
“…This proportion is less than one in five reported elsewhere but our sample included only the ED-reported injuries which itself is a significant outcome. This is consistent with another hospital-based study from Pakistan which showed that school injuries contribute towards 5% of unintentional injuries among children less than 11 years of age [20]. The National annual incident rate for school injuries in Pakistan is 1.6 per 1 000 per year [15].…”
Section: Discussionsupporting
confidence: 87%
“…Others from Pakistan have made similar observations [17] and this highlights the unsafe environment of our households and the low levels of hazard awareness among parents. In a case-control study from Pakistan, Singer and Ghaffar [18] showed that the size of the dwelling, the level of education of the mother, and the number of children in the household are significant risk factors for injury.…”
Section: Discussionmentioning
confidence: 69%
“…A hypothesis behind high rate of injuries in children at home is that they spend a considerable amount of time at home at this age. As a result, they are at higher risk of home injuries [18]. It is expected that as children grow to have age between 1-2 years the rate of accidents at home approximates its climax because children begin to move and their growth will be faster , then the rate will slowly decrease due to the lower presence at home [19].…”
Section: Discussionmentioning
confidence: 99%